2016
DOI: 10.1002/bdra.23593
|View full text |Cite
|
Sign up to set email alerts
|

A quality assessment of reporting sources for microcephaly in Utah, 2003 to 2013

Abstract: Background Obtaining accurate microcephaly prevalence is important given the recent association between microcephaly and Zika virus. Assessing the quality of data sources can guide surveillance programs as they focus their data collection efforts. The Utah Birth Defect Network (UBDN) has monitored microcephaly by data sources since 2003. The objective of this study was to examine the impact of reporting sources for microcephaly surveillance. Methods All reported cases of microcephaly among Utah mothers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…In this issue of the journal, investigators with the Utah Birth Defect Network (UBDN) evaluated their ascertainment of microcephaly (Steele et al, ). Their results demonstrated the variability of ascertainment depending on the source and method of case finding.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the journal, investigators with the Utah Birth Defect Network (UBDN) evaluated their ascertainment of microcephaly (Steele et al, ). Their results demonstrated the variability of ascertainment depending on the source and method of case finding.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 37% of microcephaly cases in this registry had a genetic anomaly and 31% were in premature infants (Graham, ). Steele et al (), reviewing data from the Utah Birth Defect Network between 2003 and 2013, reported a microcephaly prevalence rate of 8.2/10,000 live births. The case definition for microcephaly in this cohort was a head circumference < 10th percentile at birth, ≤5th percentile at 1 year of age or ≤2nd percentile at 18 months of age, or a microcephaly diagnostic code of 742.1 (Steele et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Steele et al (), reviewing data from the Utah Birth Defect Network between 2003 and 2013, reported a microcephaly prevalence rate of 8.2/10,000 live births. The case definition for microcephaly in this cohort was a head circumference < 10th percentile at birth, ≤5th percentile at 1 year of age or ≤2nd percentile at 18 months of age, or a microcephaly diagnostic code of 742.1 (Steele et al, ). Overall, the reported rates of microcephaly in the above US birth defect registries and population‐based surveillance programs varied significantly.…”
Section: Discussionmentioning
confidence: 99%
“…This is significantly smaller than normal for the person's age and sex [43,44]. In humans, microcephaly represents a severe congenital defect [45]. Two types of microcephaly are recognized.…”
Section: Microcephalymentioning
confidence: 99%
“…The other relates to a normal brain size at birth but failure to grow subsequently due to the loss of dendritic connections [46]. Some authors have classified 3 types of microcephaly on the basis of Giacomino's classification: (i) microcephalia vera, where the size of the brain remains small without any sign of injury or deformation, (ii) microcephalia spuria, which shows some pathological changes and injury to the brain, and (iii) microcephalia combinata, which reflects a small brain size with a trace of injury [45]. The etiology of microcephaly can be both genetic and non-genetic.…”
Section: Microcephalymentioning
confidence: 99%